EXTRACTION AND CHARACTERIZATION OF SOKOTO NEEM TREE (Azadirachta Indica) SEED OIL (FUDMA JOURNAL OF SCIENCES, 2025)
Neem (Azadirachta indica) is a medicinal plant known for its rich phytochemical and therapeutic potential, particularly its seed oil. This study focuses on the extraction and characterization of neem seed oil obtained through Soxhlet and traditional methods, with a focus on physicochemical properties, phytochemical content, antioxidant vitamins, and fatty acid composition. The Soxhlet method yielded significantly more oil (47.08%) than the traditional method (17.16%) (p < 0.05). Soxhlet-extracted oil exhibited significantly higher saponification (103.78mg KOH/g) and iodine values (9.05g I/100g), suggesting better suitability for industrial applications such as soap and biodiesel production. However, it showed significantly higher acid (145.11mg KOH/g) and peroxide values (408.33meq/kg), indicating increased oxidation. Phytochemical screening revealed the presence of alkaloids, phenols, flavonoids, steroids, and saponins in both extracts, with alkaloids and phenols being more prominent. Antioxidant vitamins A and E were significantly (p < 0.05) higher in traditional method extracted oil, while both extracts had low vitamin C content. Thin-layer chromatography identified predominantly present fatty acids as stearic, oleic, linoleic, and palmitic acids, consistent across both extraction methods. The results suggest that neem seed oil especially the Soxhlet extracted has high yield and may be of use in industrial application such as soap making, however, both oils require extensive processing to make them better for use in industry and.as edible oils. Further optimization of extraction techniques could enhance the yield and functional quality of neem seed oil from local neem trees.
Keywords: Azadirachta Indica; Neem seed oil; Soxhlet extraction; Phytochemicals; Antioxidant vitamins